Low risk preliminary consultation: nurses 'view in the family health strategy (Research, Society and Development, 2022)
Objectives: describe the opinion of the nurse in the Family Health Strategy on the facilitators and barriers related to low risk prenatal consultation performed by him. Method: quantitative, non-experimental, descriptive study. The data were obtained by a data collection instrument, submitted to the apparent validation and content, applied during the month of May 2018 in a municipality in the south of the State of Minas Gerais. Twelve nurses participated in the study. Results: the majority of the nurses (75,00%) believe that the consultation performed by them is able to clarify all the doubts of the pregnant women and that their knowledge is enough to perform this care. However, (91.67%) of them stated their interest in participating in training sessions, which shows that these professionals always aim for maximum improvement. Among the main positive points of the consultation were the reception and active listening. The main barrier to the consultation was the deficit in nursing diagnoses due to lack of time. Conclusion: the suggestions for improvement of the consultation were, among others, an increase in the number of professionals to avoid work overload and the implementation of Nursing Care Systematization.